Efficacy of navicular bone exicion with carpometacarpal (four-angle) arthrodesis in patients with deformative wrist arthrosis - Strafun, Sergey; Timoshenko, Sergey; Leskov, Vladimir (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Earlier, an alternative to conservative treatment of deforming arthrosis of the carpal joint was radial styloidectomy or total arthrodesis. Various variants of resection-stabilizing interventions are known today. Objective: to determine the effectiveness of the operation of the lateral bone excision with metacarpal arthrodesis in patients with carpal joint deforming arthrosis. Methods: long-term results of lateral bone excision with metacarpal arthrodesis in 21 patients with carpal joint deforming arthrosis due to pseudoarthrosis of the lateral bone, lesions of the navicular-semilunar ligament or idiopathic aseptic necrosis of the lateral bone in a ratio of 16:3:2, respectively, were analyzed. It was performed patchy capsulotomy, lateral bone excision, eliminated instability of the articular joint, resected intervertebral articular surfaces of the semilunar-capitular and crooked-semilunar part of the joint. The arthrodesis was performed using Herbert-type screws or a Spider-type plate. Performed selective denervation of the carpal joint and bone plastics of the fusion zone. The X-ray measurements of the radial-semilunatum angle and the height index of the articular joint, the dynamics of the amplitude-strength characteristics and the indexes of the upper limb incapacity by DASH were evaluated. Results: changes in the radial-semilunatum angle from –19.4° ± 7.4° to –4.67° ± 5.0°; the index of the height of the articular joint from 0.486 ± 0.010 to 0.495 ± 0.008; the strength of the cylinder capture of the brush from (45.3 ± 8.3) to (15.2 ± 4.4) kg, DASH indexes from (45.3 ± 8.3) to (16.9 ± 3.9) points. However, the amplitude of motion varied unevenly: the flexor of the carpal joint from (29.1 ± 9.3)° to (17.2 ± 7.5)° after the operation, and the expansion from (22.1 ± 9.7)° to (40.1 ± 7.4)°. Conclusions: in the long-term period (more than a year), all patients showed significant improvement of the structural-functional parameters of the upper limb in the absence of complications and repeated surgical interventions on the wrist. The results of the treatment did not depend on the nosology, which led to deforming arthrosis, and the fixation method for arthrodesis of the metacarpal joint.